Tinjauan Faktor-Faktor yang Mempengaruhi Kualitas Hidup pada Pasien TB Paru di Indonesia: Tinjauan Pustaka - Noviana, Ineke; Kody, Martha; Mila, Antonetha R H; Landi, Melkisedek (Poltekkes Kemenkes Kupang, 2021)
Background: Indonesia ranks third as the country with the most Tuberculosis sufferers in the world, after India and China, based on Global Tuberculosis. The WHO report on the condition of TB in the world in 2018 also stated that every day in Indonesia there are 301 people dying from TB. A person's perception of his life for the context of culture and life values ​​in order to achieve his life goals is the quality of life. The bad impact of this quality is manifested in the form of frustration, anxiety, fear, irritability, and prolonged anxiety that causes a person to despair or lose enthusiasm for facing the future. Objective: The aim of this study was to determine the picture of the quality of life in Pulmonary TB patients in Indonesia. Method: This type of research is a literature review that contains a description of the findings of other people's research results. Results: From 10 scientific articles that have been reviewed, it was found that quality of life can be influenced by several factors including knowledge, age, anxiety, self-efficacy, family social support, medication adherence, stress levels and depression.